Perilaku Panic Buying Mengiringi Kemunculan COVID-19? Sebuah Studi pada Awal Pandemi di Indonesia - Agung Minto Wahyu; Afifah Chusna Az Zahra; Muhammad Iqbal Fakhrul Firdaus; Aryudho Widyatno (Universitas Kristen Maranatha, 2021)
COVID-19 has an impact on society, one of which is panic buying. This study aims to get a comprehensive picture of panic buying behavior and factors that influence it in Indonesia,. The method in this research is a mixed-method which begins by distributing the survey to 418 respondents. The results obtained from the survey were then deepened using qualitative methods through interviews with six subjects. The results showed that panic buying occurred for several items that could potentially be urgently needed during a pandemic. This is in the background by the anxiety that accompanies society. However, for other items, purchases are still made in controlled conditions and as needed. The campaign not to carry out panic buying has not been fully effective. The biggest hope of the majority of the community is not in providing supplies of the goods needed, but rather for the government to increase speed in dealing with the spread of COVID-19. Keywords: panic buying, COVID-19, pandemic, consumer behavior